Employee attitude change in adopting a market orientation and integrated e-CRM in large corporations in SA - Ganesan, Keana (My University, 2018)
Within the business-to-business playing field, large corporations in South Africa have implemented and deployed Enterprise Systems like e-CRM in the hopes of improving processes, managing customer relationships and financial gains, as promised by the technologies. These organisations have a typical product-centric focus and end up using the tool for sales management and customer profitability. Without the supporting culture and mindset manifested throughout the organisation, adoption of new technologies like e-CRM and its benefits will remain an unrealised goal. Previous research conducted in the separate fields of culture and technology state that Internal Marketing strategies can be used as change management strategies in terms of either culture or technology adoption. This study explores which Internal Marketing strategies can be applied to induce an attitude change regarding the simultaneous adoption of a market orientation and an integrated e-CRM. Three peoplefocused strategies were chosen as critical success factors, namely: (i) employee involvement; (ii) inter-functional coordination; (iii) and education, training and development. They were selected based on the aim of reducing employees’ resistance to change - especially organisational culture and technology usage. This paper builds on past findings that the identified strategies will have a positive impact on the conjunctive adoption of these organisational changes. A path model incorporating SEM visual statistics is applied to investigate the hypothesised variables. The findings indicate that education, training and development has a positive and direct impact on the increased adoption, however, both employee involvement and inter-functional coordination have an indirect effect through education, training and development. These results are founded on the study of employees at varying levels of large corporations with implemented e-CRM systems, operating within the business-to-business environment in South Africa.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing.
Keywords: Customer relations--Management; Mobile communication systems--South Africa